2020
DOI: 10.1021/acs.organomet.0c00573
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Solvent-Free Preparation of Arylphosphonates ArP(O)(OAr)2from (ArO)3P via the Michaelis–Arbuzov Rearrangement

Abstract: The Pd-catalyzed Michaelis−Arbuzov rearrangement of triaryl phosphites to produce the corresponding arylphosphonates in good to excellent yields is disclosed. In comparison to the traditional methods, this new method is highly atom efficient and is general, as it can be readily extended to aryl phosphonites and phosphinites. A gram-scale reaction of (PhO) 3 P to PhP(O)(OPh) 2 with low loading of the catalyst was also demonstrated to show its potentially practical usefulness. A plausible mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Then, intermediate II could be converted into intermediate III via intramolecular electron transfer. 29 Subsequently, intermediate III could release the phenyl radical by β-scission 30 of the C–O bond assisted by a palladium catalyst, 12,31 resulting in the formation of complex IV . In the presence of NHPI or TPP, complex IV could transform into complex V , with the formation of phosphonates as a byproduct.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, intermediate II could be converted into intermediate III via intramolecular electron transfer. 29 Subsequently, intermediate III could release the phenyl radical by β-scission 30 of the C–O bond assisted by a palladium catalyst, 12,31 resulting in the formation of complex IV . In the presence of NHPI or TPP, complex IV could transform into complex V , with the formation of phosphonates as a byproduct.…”
Section: Resultsmentioning
confidence: 99%
“…11 On the other hand, the generation of aryl radicals from triphenyl phosphites (TPP) is still challenging due to their low nucleophilicity in comparison with trialkyl phosphites and the fact that it requires C–O bond activation by a transition-metal catalyst. 12 In the last few decades, catalytic C–O bond cleavage has undergone extremely rapid development in organic synthesis, in which various new chemical bond formations such as C–C and C–heteroatoms have been involved. 13 In as early as 1979, the first Ni-catalyzed C(sp 2 )–O cleavage cross-coupling reaction of aryl methyl ethers with Grignard reagents was reported by Wenkert et al 14 Then, using this logic, many strategies have been reported, particularly for the cleavage of the C(sp 2 )–O bond with metals in different organic substrates, such as phenols 15 and phenol derivatives, 16 aryl esters, 17 aryl silyl ethers, 18 aryl phosphonates, 19 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Aryl phosphonates/phosphinates have also been formed at the low temperature of 40 °C using BiCl 3 as the Lewis acid catalyst under nitrogen atmosphere [ 39 ]. Other Lewis catalysts include the Pd 2 (dba) 3 in the presence of PhOTf and in a solvent free environment for triaryl phosphite intramolecular rearrangement [ 40 ], the CeCl 3 .7H 2 O-SiO 2 [ 41 ], the CeCl 3 .7H 2 O [ 42 ], the already-mentioned ZnBr 2 [ 19 , 20 ], the NiCl 2 [ 43 ] that also allows the usage of aryltriflates as reactants [ 44 ], the InBr 3 [ 20 ], the InCl 3 that allows the reaction of N-benzyloxycarbonylaminosulfones with triethyl phosphite to generate α-amino phosphonates [ 45 ], and the NbCl 5 [ 46 ].…”
Section: Improvements In and Variations Of The Ma Reactionmentioning
confidence: 99%
“…The currently available industrial synthesis of aryl phosphonates is limited to the tedious and heavily polluting stoichiometric Friedel–Crafts processes starting from the highly toxic PCl 3 . Only recently, we developed a highly atom-efficient Pd-catalyzed Michaelis–Arbuzov rearrangement method for preparing aryl phosphonates from triaryl phosphites (Scheme C) . Since the corresponding phosphonium intermediate ArP + (OAr) 3 ·I – is difficult to rearrange, the reaction still requires high temperature (160 °C) and long time (16 h) and has a narrow substrate scope, which may lead to high cost of the method and restrict its application in industrial synthesis.…”
mentioning
confidence: 99%
“…12 Only recently, we developed a highly atom-efficient Pd-catalyzed Michaelis−Arbuzov rearrangement method for preparing aryl phosphonates from triaryl phosphites (Scheme 1C). 13 Since the corresponding phosphonium intermediate ArP + (OAr) 3 •I − is difficult to rearrange, the reaction still requires high temperature (160 °C) and long time (16 h) and has a narrow substrate scope, which may lead to high cost of the method and restrict its application in industrial synthesis. Therefore, a new efficient and practical method with a much broader scope of substrates and much milder conditions is still highly desirable.…”
mentioning
confidence: 99%